2016
DOI: 10.1155/2016/3642960
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority and Equivalence Evaluation of Clinical Performance among Computed Radiography, Film, and Digitized Film for Telemammography Services

Abstract: Objective. The aim of this study was to evaluate and compare the clinical performance of different alternatives to implement low-cost screening telemammography. We compared computed radiography, film printed images, and digitized films produced with a specialized film digitizer and a digital camera. Material and Methods. The ethics committee of our institution approved this study. We assessed the equivalence of the clinical performance of observers for cancer detection. The factorial design included 70 screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Task‐sharing and task‐shifting approaches have been used successfully in different settings to surmount the workforce shortage for breast cancer early detection, including training and centralized services. Additional support can be supplied through digital or e‐health and telemedicine 40,43‐47 …”
Section: Situational Analysismentioning
confidence: 99%
“…Task‐sharing and task‐shifting approaches have been used successfully in different settings to surmount the workforce shortage for breast cancer early detection, including training and centralized services. Additional support can be supplied through digital or e‐health and telemedicine 40,43‐47 …”
Section: Situational Analysismentioning
confidence: 99%
“…There are no (statistical or clinical) standards for defining the margin of equivalence. A previous study in another field reported that it was difficult to obtain significant results with a margin of less than 10% , so we used this value in the study. Our findings might be used as a starting‐points for defining the margin of equivalence in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the study protocol, we used several proportion non‐inferiority tests to ensure a sufficient sample size in both groups (with and without AUD) . We set the following parameters: alpha = 5%, power = 80% and margin of equivalence = 10% . We tested sensitivity values between 20 and 80% for self‐reported AUD and we used sensitivity = 50% because it was the worst scenario in term of sample size.…”
Section: Methodsmentioning
confidence: 99%
“…We used a non-inferiority test to define how many participants were needed to obtain a similar AUC as in the first validation study (Ustun et al 2017). We used alpha=5%, power=80%, margin of equivalence=10% (Salazar et al 2016), AUC=0.94 (Ustun et al 2017), and allocation ratio=1. A total of n=98 (49 participants in each group) was needed.…”
Section: Analytical Strategymentioning
confidence: 99%